EFEKTIFITAS PENERAPAN METODE CROSS-LINE TERHADAP PEMAHAMAN KONSEP PERKALIAN PADA SISWA KELAS 3 SD NEGERI 2 BUGEL - Natasya Arieni Fasya; Daniela Arnesti Nailufar; Wulan Sutriyani (LPPM Politeknik Pratama, 2023)
This research is motivated by an understanding of the material concept in multiplication which aims to evaluate the effectiveness of applying the cross-line method to understanding the concept of multiplication in grade 3 students at SD Negeri 2 Bugel. modern. This is because, because there are still many who cannot multiply, the cross-line method is a shortcut for understanding the concept of multiplication quickly. The cross-line method is a math learning technique that involves using crossed lines to help students understand the concept of multiplication. This study used a quasi-experimental method with a pretest-posttest group design. The research sample consisted of 14 grade 3 students. The results showed that the application of the cross-line method significantly increased the understanding of the concept of multiplication in grade 3 students at SD Negeri 2 Bugel. In conclusion, the cross-line method can be used as an alternative in learning mathematics to increase understanding of the concept of multiplication in 3rd grade elementary school students.